Magnetic Misalignment of Interstellar Dust Filaments - Ari J. Cukierman; S. E. Clark; George Halal (The Astrophysical Journal, 2023)
We present evidence for scale-independent misalignment of interstellar dust filaments and magnetic fields. We estimate the misalignment by comparing millimeter-wave dust-polarization measurements from Planck with filamentary structures identified in neutral-hydrogen (H i ) measurements from H i 4PI. We find that the misalignment angle displays a scale independence (harmonic coherence) for features larger than the H i 4PI beamwidth (16.′2). We additionally find a spatial coherence on angular scales of ${ \mathcal O }(1^° )$ . We present several misalignment estimators formed from the auto- and cross-spectra of dust-polarization and H i -based maps, and we also introduce a map-space estimator. Applied to large regions of the high-Galactic-latitude sky, we find a global misalignment angle of ∼2°, which is robust to a variety of masking choices. By dividing the sky into small regions, we show that the misalignment angle correlates with the parity-violating TB cross-spectrum measured in the Planck dust maps. The misalignment paradigm also predicts a dust EB signal, which is of relevance in the search for cosmic birefringence but as yet undetected; the measurements of EB are noisier than those of TB , and our correlations of EB with misalignment angle are found to be weaker and less robust to masking choices. We also introduce an H i -based dust-polarization template constructed from the Hessian matrix of the H i intensity, which is found to correlate more strongly than previous templates with Planck dust B modes.